Wnt-related SynGAP1 is a neuroprotective factor of glutamatergic synapses against Aβ oligomers - Codocedo, Juan F.; Montecinos-Oliva, Carla; Inestrosa, Nibaldo C. (Frontiers in Cellular Neuroscience, 2015)
Wnt-5a is a synaptogenic factor that modulates glutamatergic synapses and generates neuroprotection against Aβ oligomers. It is known that Wnt-5a plays a key role in the adult nervous system and synaptic plasticity. Emerging evidence indicates that miRNAs are actively involved in the regulation of synaptic plasticity. Recently, we showed that Wnt-5a is able to control the expression of several miRNAs including miR-101b, which has been extensively studied in carcinogenesis. However, its role in brain is just beginning to be explored. That is why we aim to study the relationship between Wnt-5a and miRNAs in glutamatergic synapses. We performed in silico analysis which predicted that miR-101b may inhibit the expression of synaptic GTPase-Activating Protein (SynGAP1), a Ras GTPase-activating protein critical for the development of cognition and proper synaptic function. Through overexpression of miR-101b, we showed that miR-101b is able to regulate the expression of SynGAP1 in an hippocampal cell line. Moreover and consistent with a decrease of miR-101b, Wnt-5a enhances SynGAP expression in cultured hippocampal neurons. Additionally, Wnt-5a increases the activity of SynGAP in a time-dependent manner, with a similar kinetic to CaMKII phosphorylation. This also, correlates with a modulation in the SynGAP clusters density. On the other hand, Aβ oligomers permanently decrease the number of SynGAP clusters. Interestingly, when neurons are co-incubated with Wnt-5a and Aβ oligomers, we do not observe the detrimental effect of Aβ oligomers, indicating that, Wnt-5a protects neurons from the synaptic failure triggered by Aβ oligomers. Overall, our findings suggest that SynGAP1 is part of the signaling pathways induced by Wnt-5a. Therefore, possibility exists that SynGAP is involved in the synaptic protection against Aβ oligomers.